HEALTH EDUCATION WITH A FOCUS ON CARE FOR CHRONIC DISEASES: INTERVENTION PROPOSAL - do Monte Massela Malta, Arlete; Rodrigues, Alexsandro; Zanatelli, Carla; Moraes, Gabriela; de Matia, Graciele; Cristine da Silva, Suellen; Cicero da Silva, Luciano (Health and Society, 2023)
This intervention xchang is xchang the work management and education and health research line and will seek to raise the awareness of patients with chronic diseases to adopt healthy habits, such as good nutrition, regular physical exercise practices and periodic exams to measure glycemic indexes , blood pressure, among others, through lectures, information, whether physical (pamphlets and posters) or digital (communication channels on social networks such as Whatsapp, for the exchange of information between patients and health professionals, aiming to increase well-being and quality of life as well as promoting education for the prevention of these diseases through informative actions and interventions in the population assisted in health establishments and schools.